Penggunaan Game SKIDU (Sex Kids Education) Sebagai Upaya Pengenalan Pendidikan Seks Pada Anak Usia Dini. - Indryani; Utami, Winda Sherly; Sri Indriani Harianja; Akhmad Fikri Rosyadi; Dewi Rahayu (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
The introduction of sex education is an urgency that needs to be given to children from an early age to prevent the widespread phenomenon of sexual violence that occurs in Indonesia. In addition, children's lack of understanding about sexual harassment and the dangers surrounding it makes children remain silent when abused. This research aims to analyze the influence of the SKIDU (Sex Kids Education) game as an effort to introduce sex education to children aged 5-6 years. This type of research is quantitative research. This research uses a pre-experimental method with a one-group pretest-posttest design without a control class. The sample in this study was ten children aged 5-6 years. Data collection is obtained from observation and documentation. The data collection instrument uses a questionnaire sheet. The data analysis technique uses hypothesis testing (paired sample t-test). The results obtained were differences before and after being given treatment using the SKIDU (Sex Kids Education) game. The SKIDU (Sex Kids Education) game influences introducing sex education to children aged 5-6 years. It was concluded that the use of the SKIDU (Sex Kids Education) game can increase children's knowledge about sex education. The implication of this research is that the SKIDU game can increase young children's understanding of body parts that other people should not touch.